Data analytics and pump control in a wastewater treatment plant. (1st October 2021) - Johnson, Hilary A.; Simon, Kevin P.; Slocum, Alexander H.
Abstract: This paper analyzes data from ten 2, 610 kW centrifugal pumps in a large wastewater treatment facility in order to identify efficiency opportunities, evaluate efficiency metrics, and assess applicability of operating space analysis. Three efficiency interventions are evaluated: pump maintenance, ranking and utilizing the most efficient pumps, and reducing the number of pumps operating during low flow periods. Systemic energy savings of 4.3%, 809, 000 kWh annually, were identified. Applying average and true weighted efficiency to datasets with hourly and 5 min sampling rates demonstrates the effects of efficiency metric selection. Operating space analysis is introduced as a method of intersecting pump and system spaces. It is used to evaluate how methods of pump control, such as variable speed drives, affect the performance of a system. Results show that specific energy and maximum efficiency occur at slightly different operating points in the case study example, thus illustrating the utility of specific energy in control optimizations. Operating space analysis may simplify data mining for pumped systems, improve control algorithms, and chart opportunities for next-generation control technologies and further research. Highlights: Centrifugal pumps consume 6% of annual US electricity. Quantifies interventions demonstrating 4.3% energy savings, 809, 000 kWh annually. Demonstrates effect of data sampling rate on pump efficiency calculations. Explores control of flow and efficiency beyond variable frequency drives. Operating space analysis enables robust synthesis of multidimensional pump system operation.